Cross-sectional relations of digital vascular function to cardiovascular risk factors in the Framingham Heart Study - Hamburg, Naomi M; Keyes, Michelle J; Larson, Martin G; Vasan, Ramachandran S; Schnabel, Renate; Pryde, Moira M; Mitchell, Gary F; Sheffy, Jacob; Vita, Joseph A; Benjamin, Emelia J (Circulation (New York, N.Y.), 2008)
Digital pulse amplitude augmentation in response to hyperemia is a novel measure of peripheral vasodilator function that depends partially on endothelium-derived nitric oxide. Baseline digital pulse amplitude reflects local peripheral arterial tone. The relation of digital pulse amplitude and digital hyperemic response to cardiovascular risk factors in the community is unknown. Using a fingertip peripheral arterial tonometry (PAT) device, we measured digital pulse amplitude in Framingham Third Generation Cohort participants (n=1957; mean age, 40+/-9 years; 49% women) at baseline and in 30-second intervals for 4 minutes during reactive hyperemia induced by 5-minute forearm cuff occlusion. To evaluate the vascular response in relation to baseline, adjusting for systemic effects and skewed data, we expressed the hyperemic response (called the PAT ratio) as the natural logarithm of the ratio of postdeflation to baseline pulse amplitude in the hyperemic finger divided by the same ratio in the contralateral finger that served as control. The relation of the PAT ratio to cardiovascular risk factors was strongest in the 90- to 120-second postdeflation interval (overall model R(2)=0.159). In stepwise multivariable linear regression models, male sex, body mass index, ratio of total to high-density lipoprotein cholesterol, diabetes mellitus, smoking, and lipid-lowering treatment were inversely related to PAT ratio, whereas increasing age was positively related to PAT ratio (all P<0.01). Reactive hyperemia produced a time-dependent increase in fingertip pulse amplitude. Digital vasodilator function is related to multiple traditional and metabolic cardiovascular risk factors. Our findings support further investigations to define the clinical utility and predictive value of digital pulse amplitude.